Fabrication of 3D-printed molds for polydimethylsiloxane-based microfluidic devices using a liquid crystal display-based vat photopolymerization process: printing quality, drug response and 3D invasion cell culture assays - Matthew D. Poskus; Tuo Wang; Yuxuan Deng; Sydney Borcherding; Jake Atkinson; Ioannis K. Zervantonakis (Microsystems & Nanoengineering, 2023)
Abstract Microfluidic platforms enable more precise control of biological stimuli and environment dimensionality than conventional macroscale cell-based assays; however, long fabrication times and high-cost specialized equipment limit the widespread adoption of microfluidic technologies. Recent improvements in vat photopolymerization three-dimensional (3D) printing technologies such as liquid crystal display (LCD) printing offer rapid prototyping and a cost-effective solution to microfluidic fabrication. Limited information is available about how 3D printing parameters and resin cytocompatibility impact the performance of 3D-printed molds for the fabrication of polydimethylsiloxane (PDMS)-based microfluidic platforms for cellular studies. Using a low-cost, commercially available LCD-based 3D printer, we assessed the cytocompatibility of several resins, optimized fabrication parameters, and characterized the minimum feature size. We evaluated the response to both cytotoxic chemotherapy and targeted kinase therapies in microfluidic devices fabricated using our 3D-printed molds and demonstrated the establishment of flow-based concentration gradients. Furthermore, we monitored real-time cancer cell and fibroblast migration in a 3D matrix environment that was dependent on environmental signals. These results demonstrate how vat photopolymerization LCD-based fabrication can accelerate the prototyping of microfluidic platforms with increased accessibility and resolution for PDMS-based cell culture assays.